Effect of dietary complex Chinese herbal medicine on growth performance, digestive enzyme activities in tissues and expression of genes involved in the digestive enzymes and antioxidant enzymes and bacterial challenge in Litopenaeus vannamei. (24th August 2021) - Zhang, Yu; Bian, Yunyi; Cui, Qingman; Yuan, Chunying; Lin, Yiting; Li, Jiayuan; Meng, Peirou
Abstract: The purpose of this study was to evaluate the effect of complex Chinese herbal medicines (CCHM) on growth performance, digestive enzyme activity, immunity and metabolism and Vibrio parahemolyticus resistance of Litopenaeus vannamei . The 30‐day feeding experimental results indicated that dietary CCHM obviously increased the survival rate (SR), weight gain rate (WGR) and specific growth rate (SGR) of shrimp. The feed conversion ratio (FCR) was obviously reduced by the CHMM. The supplementation of CCHM could significantly ( p < 0.05) increase the activity of protease in the stomach, hepatopancreas and intestine of shrimp. The activities of amylase and lipase were enhanced significantly ( p < 0.05) in the stomach, hepatopancreas and intestine of shrimp fed 10 g/kg CCHM diet. The number of haemocytes was increased significantly ( p < 0.05) in the shrimp fed the diet with 10 and 15 g/kg CHMM. The activities of total superoxide dismutase (T‐SOD), glutathione peroxidase (GSH‐Px) and catalase (CAT) in the hepatopancreas of shrimp fed with 10 g/kg CCHM were significantly ( p < 0.05) higher than that of the control group. The gene expression levels of SOD, CAT, ATPase, TLR, chymotrypsin and GS in the hepatopancreas and intestine of prawns fed with 10 g/kg CCHM were significantly ( p < 0.05) up‐regulated. In challenge experiment, the relative protection rate was significantly ( p < 0.05) increased in the shrimp fed CCHM‐supplemental diet when challenged with V. parahaemolyticus . Comprehensive consideration of the current experimental results, the additive suitable dosage of the CCHM was 10 g/kg.